Use of Health Services by Maltreated Children in Two Different Sociocultural Contexts: Where Can Doors for Interventions Be Opened?. Issue 12 (June 2019) - Suglia, Shakira F.; Shen, Sa; Cohall, Alwyn; Bird, Hector; Canino, Glorisa; Brown, Jocelyn; Duarte, Cristiane S.
Among maltreated children, elevated use of non-routine (for illness or injury) services may coexist with underutilization of preventive services. Besides physical health problems, lack of contact with primary care may preclude the identification and delivery of appropriate interventions. We examined health service utilization in the longitudinal Boricua Youth Study of Puerto Rican children residing in the South Bronx (SBx), New York City ( n = 901), and San Juan metropolitan area, Puerto Rico ( n = 1, 163). Parents and children ( M age = 9 years) reported on child physical abuse, sexual abuse, and neglect. Parents reported if their child had been to illness, injury, and well-child visits in the past year. In the SBx site, caretakers were more likely to report the children seeing a doctor for a well-child visit (90%) compared with children in Puerto Rico (71%). Children in Puerto Rico were more likely to visit a doctor for an injury in the past year compared with children in the SBx (39% vs. 24%). Twenty-one percent of children in the SBx reported maltreatment versus 16% in Puerto Rico. Adjusting for sociodemographic factors, compared with non-maltreated children, those who experienced two or more types of maltreatment were more likely to have an illness visit in Puerto Rico (prevalence ratio [PR] = 1.5, 95% confidence interval [CI] = [1.1, 2.2]) and the SBx (PR = 1.8, 95% CI = [1.1, 3.0]), or an injury visit (PR = 4.1, 95% CI = [1.9, 8.9]) in Puerto Rico only. Children in the SBx who reported only one type of maltreatment were less likely to use services for injuries than non-maltreated children (PR = 0.42, 95% CI = [0.2, 0.9]). No relation between maltreatment and well-child visits was noted. Children who experience maltreatment may frequently come in contact with health care providers, presenting opportunities for intervention and the prevention of further maltreatment.